Bates Motel. Season one - Gates, Tucker; Edwards, Paul (Paul A.); Farmiga, Vera; Highmore, Freddie, 1992-; Thieriot, Max; Bloch, Robert, 1917-1994 (Universal City, CA : Universal Studios Home Entertainment, 2013)
A young Norman Bates and his mother Norma move to a coastal town after the death of his father and purchase an old house and adjoining motel, but quickly find themselves in the midst of strange happenings.
First you dream, then you die -- Nice town you picked, Norma-- -- What's wrong with Norman -- Trust me -- Ocean view -- The truth -- The man in number 9 -- A boy and his dog -- Underwater -- Midnight.
Based on the characters created by Robert Bloch.
Dolby digital 5.1, wide screen 1.78:1.
Features: Paley Center panel discussion with cast and creative team; deleted scenes; UltraViolet enabled digital copy.
Vera Farmiga, Freddie Highmore, Max Thieriot, Olivia Cooke, Nicola Peltz.
Originally broadcast on television in 2013.
TV rating: Not rated.
Keywords: Bloch, Robert, -- 1917-1994 -- Television adaptations; Bates, Norman (Fictitious character) -- Drama; Motels -- Drama; Mothers and sons -- Drama; Serial murderers -- Drama; Thrillers (Television programs); Television series; Fiction television programs; Video recordings for the hearing impaired; Based on the book; Horror television programs